Cellular Biomarkers of Rejection in Lung Transplant: The Usefulness of Eosinophil and Lymphocyte Counts - Piedad Ussetti; Silvia Aguado; Rosalía Laporta (Barcelona Respiratory Network Reviews, 2023)
There is increasing interest in the development of biomarkers of acute cellular rejection (ACR) and chronic allograft dysfunction (CLAD) in lung transplant recipients. However, few studies have focused on the predictive value of cellular biomarkers usually available in routine clinical practice such as eosinophils (EOS) and lymphocytes.